English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

simplify the expression.

-2x^-2y^0


i aslo need help in this problem..

simplify the expression.

2x^2y^7/6xy^-1

2007-07-03 06:21:36 · 8 answers · asked by lost 2 in Science & Mathematics Mathematics

8 answers

Ok, first off, a quick lesson...

anything to the 0 power = 1
so...
2^0 = 1
x^0 = 1

A negative exponent basically means to "flip" the fraction.
so...
x^-1 = 1 / x
(2/3)^-1 = 3/2
(1/x)^-1 = x

Remember when you're dividing two of the same bases, you subtract exponents:
x^a / x^b = x^(a - b)

And when you're multiplying...
x^a * x^b = x^(a + b)

==================
Ok.... now:
-2 x^-2 y^0
= -2 (1/x^2) (1)
= -2 / x^2

2 x^2 y^7 / 6 x y^-1
= (2/6)(x^2 / x) (y^7 / y^-1)
= (1/3) [x^(2 - 1)] [y^7 * y^1]
= (1/3)(x^1)[y^(7 + 1)]
= (1/3)(x)(y^8)
= xy^8 / 3

2007-07-03 06:26:50 · answer #1 · answered by Mathematica 7 · 0 0

= -2x^-2 (since Y^0 = 1)

= -2 / X^2

2007-07-03 13:30:08 · answer #2 · answered by spirit dummy 5 · 0 0

-2x^-2y^0 = -2y^0/x^2 = -2/x^2

2x^2y^7/6xy^-1 = xy^8/3

2007-07-03 13:34:13 · answer #3 · answered by ironduke8159 7 · 0 0

-2x^-2 y^0
= -2/x^2 (1).....a^0=1
=-2/x^2

2x^2 y^7/6x y^-1
=2x^1 y^8/6
= x y^8/3

2007-07-03 13:29:47 · answer #4 · answered by harry m 6 · 0 0

Im assuming its supposed to be -2x^(-2y^(0))

The -2y^0 is equal to 1, so it becomes -2x^1, which equals -2x

2007-07-03 13:24:41 · answer #5 · answered by therealchuckbales 5 · 0 2

Anything raised to the Zero power is 1.

I'm not sure about your notations however...the "^" symbol is usually used to signify "to the power of".

2007-07-03 13:23:35 · answer #6 · answered by jjsocrates 4 · 0 1

plz do it your self. it is very simple math. if i tell you the anwer you will not learn any thing.

2007-07-03 13:25:25 · answer #7 · answered by Anonymous · 0 1

is it science..x= girl and y=boy??

2007-07-03 13:23:56 · answer #8 · answered by Anonymous · 0 2

fedest.com, questions and answers